2015
DOI: 10.1371/journal.pone.0126121
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Linear B-Cell Epitope of Betanodavirus Coat Protein by RG-M18 Neutralizing mAB Inhibits Giant Grouper Nervous Necrosis Virus (GGNNV) Infection

Abstract: Betanodavirus is a causative agent of viral nervous necrosis syndrome in many important aquaculture marine fish larvae, resulting in high global mortality. The coat protein of Betanodavirus is the sole structural protein, and it can assemble the virion particle by itself. In this study, we used a high-titer neutralizing mAB, RG-M18, to identify the linear B-cell epitope on the viral coat protein. By mapping a series of recombinant proteins generated using the E. coli PET expression system, we demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The evolutionary distances were computed using the Kimura 2-parameter method [26] and are in the units of the number of base substitutions per site [27][28][29][30]. GenBank accession numbers and references for nucleotide sequences are as follow: EU826138.1 [31], EF617326 [32], NC_013461 [33], KF386164 [34], KY354698.1 [35], GU826692.1 [36], HE796793.1 [37], KY354694.1 [35], HE796789.1 [37], HE796797.1 [37], HE796788.1 [37], HE796791.1 [37], HE796790.1 [37], HE796785.1 [37], HE796798.1 [37], HE796799.1 [37], HE796794.1 [37], HE796786.1 [37], AJ698093.1 [38], AF318942.1 [39], AF499774.1 [40], HE796795.1 [37], HE796796.1 [37], HE796787.1 [37], HE796784 [37], KM588181.1 [41], KP455642.1 [42], AY284968.1 [43], HE796792.1 [37], JN190021.1 [44].…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary distances were computed using the Kimura 2-parameter method [26] and are in the units of the number of base substitutions per site [27][28][29][30]. GenBank accession numbers and references for nucleotide sequences are as follow: EU826138.1 [31], EF617326 [32], NC_013461 [33], KF386164 [34], KY354698.1 [35], GU826692.1 [36], HE796793.1 [37], KY354694.1 [35], HE796789.1 [37], HE796797.1 [37], HE796788.1 [37], HE796791.1 [37], HE796790.1 [37], HE796785.1 [37], HE796798.1 [37], HE796799.1 [37], HE796794.1 [37], HE796786.1 [37], AJ698093.1 [38], AF318942.1 [39], AF499774.1 [40], HE796795.1 [37], HE796796.1 [37], HE796787.1 [37], HE796784 [37], KM588181.1 [41], KP455642.1 [42], AY284968.1 [43], HE796792.1 [37], JN190021.1 [44].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of Abs to neutralize virus is usually confirmed by the lack of a CPE in infected cells, and treatment of the neutralizing Abs can decrease the numbers of cytopathic cells, compared with the untreated conditions (25,(31)(32)(33). In general, the capacity of Abs to neutralize a virus in vitro is 1 3 10 2 TCID 50 in a neutralization test; however, the VLRBs produced in this study were able to inhibit the viral infection at ,13 10 2 TCID 50 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Nervous necrosis virus (NNV), also known as Betanodavirus, causes viral encephalopathy and retinopathy, which is an infectious disease responsible for high levels of mortality in more than 40 species of marine and freshwater fish. Infection by this virus leads to abnormal behavior and visual dysfunction, such as spiral swimming along with extensive vacuolation and neuronal degeneration (24)(25)(26). Studies cited in the previous sentence have mAbs from seabream (Sparus aurata) and giant grouper (Epinephelus lanceolatus), but our mAb against NNV was produced from hagfish (Eptatretus burgeri).…”
mentioning
confidence: 99%
“…Types I and II-IFN are present in fish [211,212] and both have been detected in individuals infected with betanodavirus [163]. I-IFN transcription has been reported to be up-regulated in sea bass [213] and grouper [212], II-IFN production increased in experimentally infected turbot [214], whereas both I and II IFN were induced in infected zebra fish [215]. IFN up-regulation has also been described in in vitro assays, in barramundi brain (BB), grouper brain (GB) and FHM cells [216][217][218].…”
Section: Host Responsementioning
confidence: 99%